Immune Response of Laying Hens Exposed to 30 ppm Ammonia for 25 Weeks - Chen, H.; Yan, F.F.; Hu, J.Y.; Wu, Yanan; Tucker, C.M.; Green, A.R.; Cheng , H.W. (International Journal of Poultry Science, 2017)
Background and Objective: Ammonia (NH3) is one of the most prominent aerial pollutants inside poultry barns, affecting chicken health and well-being based on its level and exposure duration. The aim of this study was to investigate the effect of 30 ppm NH3 on the immune response of laying hens. Methodology: Hy-Line W-36 hens at 18 weeks of age were randomly assigned to 4 hen cages and evenly distributed to two controlled environment chambers. Beginning at 25 weeks of age, one chamber was maintained continuously with fresh air (NH3 < 5 ppm; control group) and the other one was injected with NH3 and controlled at 30 ppm (NH3 group) for 25 weeks. At 50 weeks of age, plasma concentrations of total immunoglobulins (IgA, IgG and IgM), complement factors (C3 and C4), albumin (ALB), Alpha-1-acid glycoprotein (AGP) and cytokines including interleukin (IL)-1β, IL-6, interferon gamma (IFN-γ) and Tumor Necrosis Factor alpha (TNF-α) as well as mRNA expressions of IL-1β, IL-6 and TNF-α in the spleens were determined (n = 16). Results: Hens exposed to NH3 had a greater Heterophil/Lymphocyte (H/L) ratio (p